Transformational Leadership and Innovative Work Behavior: Insights From A Systematic Literature Review - Rozi Resmi Sapira; Claudia Sahetapy; Erica Awaliyah; Kholistia Ulfah Khairiah; Satriadi (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
Innovative Work Behavior (IWB) has emerged as a crucial organizational competency for maintaining competitiveness and adapting to rapid environmental changes. Despite prior research consistently recognizing transformational leadership as a significant precursor to innovative work behavior (IWB), empirical evidence remains incongruent about the processes and contextual variables that underpin this association. This research seeks to consolidate current empirical information about the influence of transformational leadership on Innovative Work Behavior and to ascertain the mediating and moderating elements that enhance this connection. A Systematic Literature Review (SLR) was performed in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) criteria. Articles pertinent to the subject, published from 2019 to 2025, were sourced from the Google Scholar, SINTA, Garuda, and Scopus databases. Nineteen papers satisfied the inclusion criteria after the screening and eligibility assessment and were included into the final evaluation. The results reveal that transformational leadership is the most thoroughly examined leadership style in IWB research and regularly exhibits a favorable correlation with workers' creative behavior. Moreover, psychological empowerment, knowledge sharing, and job engagement were identified as the predominant mediating factors, while organizational culture, organizational environment, individual characteristics, and digital readiness were determined to enhance this association. This study's originality resides in its comprehensive conceptual synthesis, which integrates leadership styles, mediating mechanisms, contextual factors, and contemporary research trends, thus providing a more holistic understanding of how transformational leadership promotes Innovative Work Behavior across various organizational contexts